Wireless Network Traffic Analysis and Troubleshooting using Raspberry Pi - Nur Haziq Mohd Safri, Mohamad; Nor Shuhadah Wan Nik, Wan; Mohamad, Zarina; Mohamad, Mumtazimah (International Journal of Engineering and Technology, 2018)
In the past five decades, computer network has kept up growing with the increases of its complexity. In such situation, the management, monitoring and maintenance of such computer network requires special attention to ensure optimal network access capability is achieved. Wireless network traffic analysis is a process of recording, studying and analyzing packets in wireless network for network performance analysis purposes. In some cases, the quality of network access performance can be very low without knowing the actual problem. Therefore, in this paper, the performance of wireless network traffic is proposed to be analyzed by using a Raspberry Pi which further able to send an alert to network admin to lessen the downtime. Raspberry Pi is a low cost, a small and portable size of a computer board that can be used to plug-in to monitor, keyboard, mouse, pen drive, etc. In this project, a MyTraceroute (MTR) program is installed on the Raspberry Pi to capture the IP of the Access Point (AP) and show packets loss percentage in the network. The results will be saved in the form of text file and sent to network admin by using email. The solution proposed in this paper is able to support solution to a problem on efficient monitoring, managing and maintaining wireless network traffics. Â Â Â